2003
DOI: 10.1677/jme.0.0310449
|View full text |Cite
|
Sign up to set email alerts
|

Threshold effects of glucose transporter-4 (GLUT4) deficiency on cardiac glucose uptake and development of hypertrophy

Abstract: The aim of this study was to investigate the metabolic and structural consequences of a decrease in glucose transporter-4 (GLUT4) levels on the heart. The CreLoxP system was utilised to delete GLUT4 in muscle tissue including heart. The presence of the PGK-neoR cassette in the GLUT4-Lox mice resulted in reduced expression in all tissues to levels 15-30% of wild-type control mice. In mice expressing Cre recombinase, there was a further reduction of GLUT4 in cardiac tissue to almost undetectable levels. Cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 29 publications
3
42
0
Order By: Relevance
“…Myoblast/ myofiber-specific mAR ΔZF2 mice were generated using the α-actin-cre line (Kaczmarczyk et al 2003). The human skeletal α-actin promoter is expressed in myoblasts and myofibers (Schwander et al 2003), and results in deletion of AR in both myoblasts and myofibers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myoblast/ myofiber-specific mAR ΔZF2 mice were generated using the α-actin-cre line (Kaczmarczyk et al 2003). The human skeletal α-actin promoter is expressed in myoblasts and myofibers (Schwander et al 2003), and results in deletion of AR in both myoblasts and myofibers.…”
Section: Resultsmentioning
confidence: 99%
“…Muscle creatine kinase (MCK) mAR ΔZF2 mice were generated using the MCK-cre line (Bruning et al 1998) (a kind gift of C Ronald Kahn, Joslin Diabetes Center, Boston, MA, USA), which uses the MCK promoter to drive cre expression in postproliferative myofibers. α-actin mAR ΔZF2 mice were generated using our previously described α-actin cre line (Kaczmarczyk et al 2003), which uses the human α-skeletal actin promoter to drive cre expression in myoblasts. All mouse lines were back-crossed to a congenic C57BL/6 background (>10 generations back-cross), and control littermates (AR lox hemizygous males, cre heterozygous males and wildtype (WT) males) were used for both lines.…”
Section: Micementioning
confidence: 99%
“…One proposed pathophysiological mechanism is that the long-term toxicity of high glycemia could increase the deposition of advanced glycation end products (AGEs) in myocardial cells and bring more cross-links between collagen and elastin, causing lower flexibility but greater stiffness in the myocardium [24]. Furthermore, hyperglycemia could also damage myocardial systolic function in many other ways, such as oxidative stress, inhibiting glucose transporter expression [25], impairing calcium homeostasis [26], changing myosin ATPase conformation [27], and over-activating protein kinase C [28]. Therefore, hyperglycemia became the primary factor affecting myocardial systolic function in diabetic patients.…”
Section: Factors Influencing Systolic Function In Diabetic Patientsmentioning
confidence: 99%
“…The increase of oxidative stress may not only stimulate cardiac hypertrophy but also promote fibrosis formation (57,97,98). Our data is supported by a cardiac insulin resistance study in which hearts with Glut4 knockout showed cardiac hypertrophy, impaired contractility and increased fibrosis (18,35,40) Human studies show that failing hearts have a lower PCrl ATP ratio, which is a marker of energy reserve and a predictor of mortality (69). The PCrl A TP ratio was significantly decreased in Mb-TAC hearts compared to FVB-TAC hearts ( Figure 5).…”
Section: Cardiac Structural Remodeling and Dysfunction After Tacsupporting
confidence: 75%
“…Most efforts to inhibit cardiac glucose metabolism have utilized knockdown of one of the cardiac glucose transporters (18,40) but control of glycolysis is actually shared by several reactions (43). One of these reactions is carried out by 6-phosphofiucto-l-kinase (PFKl) (33 , 70).…”
Section: Introductionmentioning
confidence: 99%